2017
DOI: 10.1177/1090198117736346
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Treatment Adherence With the Health Belief Model in Children With Cystic Fibrosis

Abstract: These findings provide further support for the HBM in evaluating pediatric adherence, with evidence that barriers and cues to action may be targets for early intervention. Future research using this model to identify a comprehensive way to assess, understand, and elicit change in the adherence to medical regimens for youth with chronic illness would be beneficial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 52 publications
2
14
0
Order By: Relevance
“…The rates of parents’ adherence to the NDT and BMPS exercises were similar, although the adherence rates for flexibility exercises was lower. This variability among the types of exercises is consistent with the variability reported among therapeutic modalities of medical treatments for children with chronic illnesses [8,21].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The rates of parents’ adherence to the NDT and BMPS exercises were similar, although the adherence rates for flexibility exercises was lower. This variability among the types of exercises is consistent with the variability reported among therapeutic modalities of medical treatments for children with chronic illnesses [8,21].…”
Section: Discussionsupporting
confidence: 84%
“…According to evidence from qualitative research [6,7], it is suggested that instead of performing the whole home program, caregivers usually choose those activities that are easiest for them. For example, studies on cystic fibrosis have shown that there are different levels of adherence to different parts of a home therapeutic regime, such as pharmacological treatment, nutritional prescriptions and exercise [8].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers who examined this issue in 12 African countries reported high frequency of poor adherence among patients with hypertension [ 15 ]. These findings support the understanding that non-adherence is significant public health problem contributing to increased mortality, morbidity, and to excessive health care expenditure while decreasing quality of life for the population [ 16 ].…”
supporting
confidence: 81%
“…In Kampala, Uganda, 17% of stroke survivors reported adherence to their prescribed antihypertensive medications; researchers cite lack of knowledge as the main contributor to the poor adherence [ 19 ]. Despite medication adherence being key area of interest among practitioners and researchers, a gold standard intervention does not exist [ 16 ]. The aim of this study was to understand from participants’ perspectives what factors create challenges and barriers to hypertension treatment adherence and what factors facilitate treatment adherence.…”
mentioning
confidence: 99%
“…[11] The Health Belief Model (HBM) has been widely used in health behavior research to guide interventions for health behavior change. [13][14][15][16] The HBM has three main components: modifying factors, individual factors and action. [17] Modifying factors include demographic and socio-economic characteristics and knowledge on disease.…”
Section: Introductionmentioning
confidence: 99%